Educations Guidelines: Objektivitas Kritis Pendidikan Seni - Sulistyo, Rizky; Asbari, Masduki; Nur Aripin, Muhamad (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to present a video review with critical reading with the title Current Education Problems by Satu Persen – Indonesia Life School. Descriptive qualitative research methods were used to analyze the video content. The results of the study show that this video requires looking at the problems that exist in the current education system regarding the importance of school and real life which will have an impact on future life, of course also with a fraction of a percent improvement to advance the current education system, namely by showing the positive side of things that will have an impact on good habits, creating creativity and innovation that will support changing these positive habits.